Identifying antecedents in fostering work engagement among employees in public sector - Zakaria, Zaki; Idris, Khairuddin; Abu Samah, Bahaman; Zainal Abiddin, Norhasni (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Many organizations either in public or private sector are facing engagement issues in their respective departments. Despite plenty of benefits on work engagement, it is a shocking truth to find out that engagement level among employees worldwide remains poor. Malaysia is even performing worse with having among the highest percentage of disengaged employees in the world. Several other studies also confirmed this finding by stating Malaysian employees recorded low percentage of having engaged workforce. The public service is not an exception. As Malaysia is aiming high in becoming an advanced nation in 2020, this issue indeed need urgent attention from top management level in public service. More importantly, public workforce has been identified as the primary facilitators in implementing various government transformational initiatives towards achieving this noble dream. Many studies pointed out that work engagement is a good predictor for excellence performance. This unique construct can lead to higher productivity, generate customer satisfaction, promoting both in-role and extra –role behaviour and even stimulate innovation among employees. On the other hand, having disengaged employees are associated with many negative consequences such low productivity, high turnover, setting bad examples to co-workers and drive customers away through poor services. Hence, identifying antecedenst that can boost work engagement in public service is vital towards recording significant positive impact. Studies have revealed that some variables such as personal resources, job resources and transformational leadership have proven track record in fostering work engagement and thus leading towards significant positive result for individual and organizations.